The Effectiveness of the Market Day Learning Model to Foster Entrepreneur Character in Early Childhood Education - ST. Ummi Hanik; Sri Utaminingsih; Muchammmad Widjanarko (Journal of Psychology and Instruction, 2022)
Conventional learning models that still need to be used cannot foster students' entrepreneurial character. Learning is only teacher-centered, making students passive objects in the teaching and learning process. This study aims to create a guidebook for the market day learning model to foster entrepreneurial character in early childhood. This type of research uses the R & D method and refers to the theory of Borg and Gall. The data collection techniques used are interviews, observations, and questionnaires using qualitative and quantitative analysis, including analysis of market-day learning models, learning observations, and product validation. The research subjects used 15 children and one teacher. The feasibility test results validated by material experts on the learning model presented in book form scored 88 points with an average final score of 3.25. In contrast, the results of language validation by subject teachers were lower than 13 statements in the product evaluation questionnaire. 44 points. The average final score is 3.30. From these results, all were declared feasible. Based on the N-gain calculation from the field test in Kindergarten, there was an increase of 53.3%, and Kindergarten and Al Ishlah also experienced an increase of 53.3%, so based on these calculations, the product of the market day learning model is to be like declared valid. The study results indicate the need for a learning model that can foster entrepreneurship.